2018
DOI: 10.3390/nu10030384
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Jojoba Seed Extracts on Hyperglycemia-Induced Oxidative Stress in RINm5f Beta Cells

Abstract: Hyperglycemia occurs during diabetes and insulin resistance. It causes oxidative stress by increasing reactive oxygen species (ROS) levels, leading to cellular damage. Polyphenols play a central role in defense against oxidative stress. In our study, we investigated the antioxidant properties of simmondsin, a pure molecule present in jojoba seeds, and of the aqueous extract of jojoba seeds on fructose-induced oxidative stress in RINm5f beta cells. The exposure of RINm5f beta cells to fructose triggered the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 85 publications
1
14
0
Order By: Relevance
“…In a previous study, we have already demonstrated in vitro the protective effect of Jojoba seed extracts against hyperglycemia-induced oxidative stress through the modulation of RINm5f beta cell cytotoxicity, generation of ROS, insulin release, caspase-3, activation, pro-oxidant and antioxidant defense, and status of the cells. Using this elegant in vivo insulin resistance model, our purpose is to demonstrate the efficiency of jojoba seeds [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we have already demonstrated in vitro the protective effect of Jojoba seed extracts against hyperglycemia-induced oxidative stress through the modulation of RINm5f beta cell cytotoxicity, generation of ROS, insulin release, caspase-3, activation, pro-oxidant and antioxidant defense, and status of the cells. Using this elegant in vivo insulin resistance model, our purpose is to demonstrate the efficiency of jojoba seeds [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study [18], we have demonstrated that extraction of jojoba seeds by distilled water endorses different classes of polyphenols such as hydroxybenzoic acid, flavonoids, anthocyanins and hydroxycinnamic acids. For the first time, this study showed hypoglycemic and antioxidant effects, of simmondsin and aqueous extract, on Rin m5f cells.…”
Section: Introductionmentioning
confidence: 95%
“…Extracts from jojoba seed, containing a wide range of phenolic compounds, demonstrated an active free radical scavenging ability leading to improved β-cell protection [83]. A study using rat cells (RINm5f) demonstrated that jojoba seed crude extracts significantly reduced ROS levels by 69% when compared to simmondsin, the major phenolic compound found in jojoba [78]. This pattern was also reflected in caspase activation, antioxidant activity and pro-oxidant signalling pathways, where the crude extracts significantly increased the expression of Nrf2 while simmondsin displayed no effect.…”
Section: Polyphenols and Gene Modulations On β-Cell Dysfunctionmentioning
confidence: 99%
“…Nrf2 plays a key role in antioxidant defence, while p22phox activates NADPH oxidase, generating excessive ROS [84,85]. The regulation of both genes by jojoba seed extracts preserved β-cell function demonstrated by increased insulin secretion [78].…”
Section: Polyphenols and Gene Modulations On β-Cell Dysfunctionmentioning
confidence: 99%
“…The effect of extracts was evaluated on insulin secreting cell lines according to the method described by Auberval and slightly modified by Belhadj et al [29,30]. Briefly, a rat insulinoma cell line (RINm5f beta) was purchased from the American Type Culture Collection (ATCC, Manassas, VA, USA).…”
Section: Cell Viability Testmentioning
confidence: 99%